Examining the Causes of Poor Performance in Primary Schools in Rubanda District - Arineitwe, Obadia. (Kabale University, 2025)
This study aimed to identify and address the underlying factors contributing to poor performance in primary schools within Rubanda District. The objectives were to assess current academic performance trends, explore methods for controlling poor performance, and propose recommendations to enhance educational outcomes. Utilizing both qualitative and quantitative research approaches, data were collected through interviews and self-administered questionnaires from a sample of 80 respondents, including pupils, teachers, head teachers, and parents across five primary schools. The findings revealed a mixed trend in academic performance, with some schools showing improvement while others faced ongoing challenges. Key strategies identified for controlling poor performance included enhancing student support services and investing in professional development for teachers. Recommendations emphasized the importance of increasing resource allocation, implementing comprehensive teacher training programs, strengthening parental involvement, and introducing targeted remedial support programs. Improved school management practices were also highlighted as crucial for effective implementation of educational strategies. The study concluded that a balanced approach integrating enhanced resources, teacher development, and active parental engagement was necessary to address academic performance issues. By adopting these recommendations, Rubanda District's primary schools could significantly improve student outcomes and establish a more effective educational framework.